2022
DOI: 10.1039/d2ta02520e
|View full text |Cite
|
Sign up to set email alerts
|

A freestanding 3D heterophase tungsten disulfide-based aerogel as an ultrathin microwave absorber in the Ku-band

Abstract: Ingenious dielectric tuning strategy is still challenging for high-efficiency microwave absorbing (MA) materials with strong absorption at the ultrathin absorber level. In this work, the aerogel with a dual three-dimensional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The EMW absorption performance of an absorber can be characterized by using the attenuation constant ( α ), which can be expressed as: 15,40 …”
Section: Resultsmentioning
confidence: 99%
“…The EMW absorption performance of an absorber can be characterized by using the attenuation constant ( α ), which can be expressed as: 15,40 …”
Section: Resultsmentioning
confidence: 99%
“…The degree of impedance matching is expressed by | Z i n / Z o | . When the value of | Z i n / Z o | is close to 1, almost all EMWs can enter the absorbing material. It can be observed that S3 has higher impedance matching in the frequency range of 11.52–16 GHz (Figure S9, Supporting Information). Obviously, S3 can obtain sufficiently high EMW absorption at a relatively thin thickness.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Meanwhile, numerous heterointerfaces can offer more conductive paths for electron transfer, i.e., the migration of electrons in PC@IC, and the hopping of electrons by the physical contacts among the adjacent carbon-based materials, which was benecial to the absorber with a high conductivity loss. 14,27 In addition, the heterointerfaces coupled with a core-shell structure and micro-mesoporous characteristics were also potential factors for strengthening the dielectric loss, 6 and because of this several obvious resonant uctuations Fig. 3 (a-e) The 3D RL-f curves, and (f-i) the contour mapping of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…, the migration of electrons in PC@IC, and the hopping of electrons by the physical contacts among the adjacent carbon-based materials, which was beneficial to the absorber with a high conductivity loss. 14,27 In addition, the heterointerfaces coupled with a core–shell structure and micro-mesoporous characteristics were also potential factors for strengthening the dielectric loss, 6 and because of this several obvious resonant fluctuations can be noted in the ε′′ – f curves. On the other hand, it was clear that the value of μ′ for the N-IC/Co displayed certain advantages (Fig.…”
Section: Resultsmentioning
confidence: 99%